Endoscopic vs. microscopic tympanoplasty in children: a retrospective case-control study - Fink, Raffael; Beckmann, Sven; Sheppard, Sean C.; Caversaccio, Marco; Anschuetz, Lukas (Frontiers in Surgery, 2025)
PurposeTo compare the outcomes of endoscopic and microscopic tympanoplasty (TPL) types I-III in pediatric patients.MethodsA retrospective case-control study was conducted on 70 TPL cases in 58 pediatric patients at Inselspital, Bern University Hospital, Switzerland, from June 2017 to December 2023. Data on hearing function, graft intake, residual disease, operating time and complications were collected.ResultsWe observed mean postoperative air-bone gap (ABG) of 16.83 dB using the endoscopic and 19.37 dB for the microscopic techniques, as well as a higher graft intake rate (91%) for the endoscopic compared to the microscopic group (80%), although these differences did not reach statistical significance. No residual cholesteatoma was found in the endoscopic group, while the microscopic group had a significantly higher incidence of residual disease (42%; p = .03). The mean operative time was shorter in the endoscopic group (87 min vs. 113 min; p < .01). Postoperative complications were lower in the endoscopic group compared to a 14% incidence in the microscopic group.ConclusionEndoscopic tympanoplasty in pediatric patients achieves similar audiological outcomes and graft intake rates compared to the microscopic approach while offering significant advantages, including reduced operation times and lower complication rates. This minimally invasive approach is highly effective especially regarding cholesteatoma resection and provides excellent functional and structural outcomes.